Pengembangan Instrumen Tes Berbasis Literasi Saintifik Materi Alat Indra Manusia Kelas IV Sekolah Dasar - Julita Julita; Endang Widi Winarni; Irwan Koto (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2022)
This study aims to (1) describe the characteristics of the scientific literacy question instrument for human senses for fourth grade elementary school students. (2) Describing the feasibility of the scientific literacy question instrument for human senses for fourth grade elementary school students. (3) Describe the results of teacher and student responses to scientific literacy questions on human sense tools for fourth grade elementary school students. This type of research is Research and Development (R&D). The research subjects were fourth grade students of SD Negeri 1 Karang Jaya. The methods used include tests, questionnaires, and documentation. The test instrument developed is in the form of a discourse description test that includes four categories of scientific literacy. The results of the characteristics of the scientific literacy-based test instrument are, there are four question indicators with the number of scientific literacy test questions developed as many as 20 essay questions. The questions have a scientific literacy category, and are associated with everyday life. Items have different levels of difficulty and scoring. Scientific literacy-based test instrument serves to measure the level of understanding of students. The feasibility of the developed test instrument was declared valid. The reliability of the scientific literacy-based test instrument developed in the reliable category.